Generation mean analysis of yield and mineral nutrient concentrations in peanut (Arachis hypogaea L.): GENERATION MEAN ANALYSIS OF YIELD AND MINERAL NUTRIENT CONCENTRATIONS IN PEANUT - B C AJAY; H N MEENA; A L SINGH; M C DAGLA; NARENDRA KUMAR; S K BERA; K GANGADHAR; A D MAKWANA (Journal of Oilseeds Research, 2018)
Present study was undertaken to study the inheritance pattern of yield and mineral nutrients (Iron, Phosphorus, Potassium and Zinc) using five parameter generation mean analysis (P1, P2, F1, F2 and F3) in two peanut crosses(Girnar-3 × FDRS-10 and TG-37A × FDRS-10). Scaling and joint scaling tests were significant for most charactersstudied indicating that additive-dominance model alone is not enough to explain the inheritance of characters studied. Both additive and dominance variance played important role for most of the traits. Traits PY, HY, HKW, SHP andRDWare governed by additive gene whereas Kshoot , Kroot, Feshoot, Feroot, Pshoot and Proot were governed by both additive and non-additive gene effects. Positive estimates of ’i’ for Zn, K and P in cross-1 (Girnar-3 × FDRS-10) indicates that parents employed were phenotypically diverse. Therefore cross-1 holds better chance for identifying genotypes with highmineral concentrations without compromising yield levels. Hence, pedigree method of breeding could be followed for improving yield and selection could be followed in later generation when population is stable to select genotypes with high mineral concentrations.